2021
DOI: 10.21512/tw.v22i1.7019
|View full text |Cite
|
Sign up to set email alerts
|

Does Discount Matter in Indonesia e-Wallet Race? A Qualitative Study on Generation Z e-Wallet Preferences During Pandemics

Abstract: The research aimed to examine the intention of Generation Z when using e-wallet for payments and the influence of discounts towards using e-wallet in the time of pandemics. The research used the qualitative method with total data of 22 students, collected using in-depth interviews through WhatsApp free call. The result shows that discount gives an impact on Generation Z in choosing the e-wallet, but a long-term loyalty is not guaranteed. The finding demonstrates that there are other influential factors for Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
1
13
0
1
Order By: Relevance
“…(Interview 27,Zain) In line with the previous research, e-wallet is being used as a mode of transactions amongst youngsters, millennials, and generation Z altogether (Monilakshmane, 2019) (Daqar, 2020) (Persada, 2021). The main factors in using e-Wallet, namely discount (Prasasti, 2021); ease-of-use (Daqar, 2020); seemingly good idea (Persada, 2021); and the quality of mobile application (Phuong, 2020). In this study, the author found three striking answers from the interviewee.…”
Section: Interviewer: What Is the Reason Why You Used E-wallet During The Pandemics?supporting
confidence: 62%
See 1 more Smart Citation
“…(Interview 27,Zain) In line with the previous research, e-wallet is being used as a mode of transactions amongst youngsters, millennials, and generation Z altogether (Monilakshmane, 2019) (Daqar, 2020) (Persada, 2021). The main factors in using e-Wallet, namely discount (Prasasti, 2021); ease-of-use (Daqar, 2020); seemingly good idea (Persada, 2021); and the quality of mobile application (Phuong, 2020). In this study, the author found three striking answers from the interviewee.…”
Section: Interviewer: What Is the Reason Why You Used E-wallet During The Pandemics?supporting
confidence: 62%
“…While there are a few articles on generation Z or undergraduate students, the finding discussed addressed several main topics using the theory of planned behavior (Persada, 2021), and strategically focused on customer satisfaction in certain regions such as India (Dhanda, 2018). Author has also conducted preliminary research that found out that e-wallet usage in Indonesia is widespread amongst generation Z, with discounts as the underlying factors of choosing the ewallet (Prasasti, 2021). Indonesia also has key players in an e-wallet, namely OVO, GoPay, ShopeePay, Dana, and Link Aja (Daily Social, 2020), with the total monthly active users combined accounting for To reduce the gap in the literature and see the massive number of users in Indonesia, it aims to dig deeper into the phenomenon happening in Indonesia where undergraduate students (under 25 years old) are easily and conveniently use e-wallet as one of their transaction methods.…”
Section: Introductionmentioning
confidence: 99%
“…Variabel prediktor lainnya yang kuat mempengaruhi minat milenial sorong menggunakan dompet digital adalah promosi. Penelitan ini menguatkan hasil penelitian sebelumnya yang menunjukkan bahwa promosi berpengaruh secara signifikan terhadap penggunaan dompet digital (Fikri et al, 2020;Acelian et al, 2021;Pham et al, 2021;Prasasti, 2021).…”
Section: Gambar 2 Hasil Evaluasi Model Strukturalunclassified
“…Moreover, promoting customers' familiarity also will increase the perceived use and perceived usefulness of the e-wallet (Phuong et al, 2020). According to Prasasti, Aulisaina, and Hakim (2021), familiarity with the platform and features of an e-wallet can strengthen the users' loyalty to their favorite platform. Nevertheless, the outlook for familiarity with e-wallet remains strong because of the increased e-commerce popularity in recent years (Alam, Awawdeh, & Muhamad, 2021).…”
Section: Familiaritymentioning
confidence: 99%